Jak rozmawiać o prawach dziecka z przedszkolakami – na przykładzie programu edukacyjnego „Kolory Dzieciństwa” - Dziel-Sierszuła, Magdalena (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The article raises the issue of children’s rights. The main question it seeks to address is whether children should be taught about their human rights and if so, by what means. The article presents the basic assumptions of the innovative curriculum „Colours of childhood”, which outlines how the subject of children’s rights can be implemented into the teaching practice. The last part contains the results of brief survey of teachers and parents concerning the evaluation the curriculum „Colours of childhood”.